COVID-19 Vaccination Rates in a Global HIV Cohort. (18th November 2021) - Fulda, Evelynne S; Fitch, Kathleen V; Overton, Edgar T; Zanni, Markella V; Aberg, Judith A; Currier, Judith S; Lu, Michael T; Malvestutto, Carlos; Fichtenbaum, Carl J; Martinez, Esteban; Umbleja, Triin; Douglas, Pamela S; et al.
Abstract: Little is known regarding coronavirus disease 2019 (COVID-19) vaccination rates in people with HIV (PWH), a vulnerable population with significant morbidity from COVID-19. We assessed COVID-19 vaccination rates among 6952 PWH in the Randomized Trial to Prevent Vascular Events in HIV (REPRIEVE) compared to region- and country-specific vaccination data. The global probability of COVID-19 vaccination through end of July 2021 was 55% among REPRIEVE participants with rates varying substantially by Global Burden of Disease (GBD) superregion. Among PWH, factors associated with COVID-19 vaccination included residence in high-income regions, age, white race, male sex, body mass index, and higher cardiovascular risk. Clinical Trials Registration. NCT02344290.